Assess economic and environmental trade-off for inland port location. (22nd April 2019) - Chang, Zheng; Weng, Jinxian; Qi, Zhuang; Yang, Dong
This paper proposes a multi-objective optimisation model to study the inland port location in a multimodal hinterland freight network. The model takes the different preferences of various stakeholders into consideration through minimising the transportation cost for shippers, the fixed cost of inland port operator and the CO2 emissions for community simultaneously. A NSGA II- solution algorithm is applied to find the Pareto optimal solutions for the multi-objective optimisation model we built. A case study using actual data is conducted to validate the model and the solution method in the end. The empirical results indicate that in most cases the transportation cost and emissions decrease when more inland ports are constructed, but this is not conclusive, in few cases we find more inland ports lead to increased transportation cost. Furthermore, the construction of inland ports generates greater relative gains in environment than that in shippers' economic benefit.